Changing Landscapes: The Construction of Meaning and Value in a New Market Category—Modern Indian Art - Khaire, Mukti; Wadhwani, R. Daniel (Academy of Management Journal, 2010)
Stable category meanings act as institutions that facilitate market exchange by providing bases for comparison and valuation. Yet little is known about meaning construction in new categories or how meaning translates into valuation criteria. We address this gap in a descriptive study of these processes in an emerging category: modern Indian art. Discourse analysis revealed how market actors shaped the construction of meaning in the new category by reinterpreting historical constructs in ways that enhanced commensurability and enabled aesthetic comparisons and valuation. Analysis of auction transactions indicated greater intersubjective agreement about valuation over time as the new category institutionalized.